SISTEM INFORMASI ADMINISTRASI SURAT TINGKAT RT BERBASIS WEB (STUDI KASUS RT 040 KELURAHAN PESAWAHAN) - Kenny Claudie Fandau; Akmal Junaidi; Kurnia Muludi (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Reference letters play an important role in the management of population administration at the sub-district (kelurahan) level. When the residents need a reference letter for their specific purpose, they first must manage the request letter from RT and deliver it to the sub-district office. However, during the COVID-19 pandemic, direct interaction among residents and sub-district officers should be avoided. Even, in some circumstances, the services by the sub-district office must be performed online. For this reason, a web-based RT Level Letter Administration Information System was developed by applying the waterfall approach. The user interaction and communication are modeled by Unified Modeling Language (UML). The system is implemented using PHP. The assessment of the functionality of the system by the Black Box Testing indicates that the system conforms to its requirements. This system is ready to deploy in RT 040 of sub-district Pesawahan, Bandar Lampung to serve residents.